Pencegahan Pengendalian Infeksi Covid-19 dengan Menjadi Vaksinator Covid-19 Pada Masyarakat di Wilayah Kerja Puskesmas II Denpasar Selatan - Putu Ayu Ratna Darmayanti; Ni Komang Sri Ariani; Wulan Tertiana Santhi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
The government has targeted for the entire community to get vaccination to lower the COVID-19 pain and death figures. Indonesia's COVID-19 vaccination for the general public is given as much as 2 times with a diverse vaccine type with a 0.5 ml dose of administration. However, the reality of the vaccinator power field is experiencing fatigue from the lack of HR. The aim of this activity was to assist vaccinator power, increase vaccination coverage and succeed government programs to suppress the death rate due to COVID-19. Devotion to the community with COVID-19 vaccinator activities in the working area of Puskesmas II Denpasar Selatan was conducted for 1 week on September 13–17, 2021. The initial stage was made an approach on the head of Puskesmas II Denpasar Selatan and the chairman of the COVID-19 vaccinator team and conducted the briefing before starting vaccination. Then, continued with vaccination activities on table 1 and 2, providing satisfaction level questionnaires on the community who had been obtaining vaccination in the observation room for 30 minutes. The servicer activity was conducted on 750 people of the community in the South Denpasar II Puskesmas working area for 1 week. The result earned was that of most of the communities that followed the activities of the 31-59-year-old COVID-19 vaccination of 46.4%. Most are female-sex 51.9% and most are high school-educated at 42.3%. The level of community satisfaction at the service of the COVID-19 vaccinator in the South Denpasar II Public Health Center that is almost the entire community is satisfied by 78.51%. COVID-19 Vaccinator activity was significantly influential to the increased scope of vaccination participants daily targets. It is expected that the COVID-19 vaccinator officer can continue to cooperate with the health college in the hosting of vaccination by keeping compliance with health protocols. Keyword: COVID-19 Vaccination, Vaccinator, Prevention, Control